The Structure of Noun Phrases in Novel Synopsis by Jenny Han - Putri, Anisah; Setia, Eddy; Nurlela, Nurlela (Politeknik Harapan Bangsa Surakarta, 2022)
This study aimed to find various forms of noun phrase structures and found the most dominant noun phrases used. To solving the problem, the researcher used Burton's theory. In addition, descriptive qualitative used by the researcher to analysing the data. This analysis used a tree diagram to see the detailed structure of the noun phrase used in the synopsis of the novel. The data used was a synopsis of novels written by Jenny Han, including,Â To All the Boys series and Summer I Turned Pretty series. This analysis found seven types of noun phrase structures consisting of Determiner + Head, Premodifier + Head, Head + Postmodifier, Determiner + Premodifier + Head, Determiner + Head + Postmodifier, Premodifier + Head + Postmodifier and Determiner + Premodifier + Head + Postmodifier. Last, the researcher found that the most used structure of noun phrases is Determiner + Head + Post modifier with 28%.